Supporting Civil Society - Macdonald, Laura. author. aut Link
XV, 195 p.
Keywords: Many analysts are looking to non-governmental organizations (NGOs) as the promoters of more equitable and democratic forms of development because of their status as actors in civil society. Based on a critical evaluation of six rural development projects in Costa Rica and Nicaragua, Supporting Civil Society shows that NGOs often perpetuate paternalism and dependency. It is argued that both international and national NGOs need to support social movements which are best able to express the demands of people at the grassroots.